TiCl4-n-Bu3N-mediated cascade annulation of ketones with alpha-ketoesters: a facile synthesis of highly substituted fused gamma-alkylidene-butenolides - Palange, Megha N.; Gonnade, Rajesh G.; Kontham, Ravindar (Organic & Biomolecular Chemistry, 2019)
A facile protocol for the synthesis of highly substituted fused gamma-alkylidene butenolides using direct annulation of ketones with alpha-ketoesters, which proceeds through TiCl4-n-Bu3N mediated aldol addition followed by an intramolecular enol-lactonization/cyclization cascade, is reported. Diverse 6-5, 7-5 and 8-5 fused bicyclic gamma-ylidene butenolides and highly substituted monocyclic analogs related to biologically relevant natural products were prepared from readily accessible ketone and alpha-ketoester building blocks. The highly step-economic cascade nature, good substrate scope, easy access to complex products with good to excellent yields, gram-scalability, demonstration of synthetic utility, and unambiguous structural confirmation through X-ray crystallography analyses and analogy are the salient features of this work.

Total synthesis of beshanzuenone D and its epimers and abiespiroside A - Borade, Balasaheb R.; Dixit, Ruchi; Kontham, Ravindar (Organic Letters, 2020)
A unified and protecting-group-free six-step total synthesis of bisabolane-type sesquiterpenoid beshanzuenone D and its stereoisomers and abiespiroside A using S-(+)-carvone as a common chiral-pool building block is disclosed. This synthetic route features chemoselective allylic chlorination of carvone, Au(I)-catalyzed cydoisomerization induced construction of furan from homopropargylic diol, substrate-controlled selective hydroxylation using Davis-oxaziridine, and dye-sensitized photo-oxidation (through O-1(2)) of hydroxyalkyl tethered furan to access oxaspirolactone as key transformations. A comprehensive set of NMR data along with DFT calculations, ECD spectra, and optical rotation measurements of the synthesized beshanzuenone D and its epimers were obtained to confirm absolute configurations.

Total synthesis of linear lipodepsipeptide kavaratamide A and its C25-epimer - Sahu, Manas Ranjan; Ingale, Sudhir R.; Kontham, Ravindar (Organic & Biomolecular Chemistry, 2025)
We report the stereoselective total synthesis of kavaratamide A, a linear lipodepsipeptide from the cyanobacterium Moorena bouillonii (collected in Kavaratti, India), and its unnatural C25-epimer. The convergent approach employs Keck asymmetric allylation to construct the chiral beta-hydroxy carboxylic acid fragment [(3S)-HDA; 3-hydroxydecanoic acid], while the peptide unit was assembled from l-Val, N-Me-l-Ala, (S)-Hiva, and (S)-iPr-O-Me-pyr using well-orchestrated coupling methods to prevent racemization. Modifications to the Keck allylation conditions enabled the synthesis of the C25-epimer with good yield. Cytotoxicity of kavaratamide A and C25-epi-kavaratamide A, assessed using the MTT assay, demonstrated moderate activity against HepG2 and PANC-1 cell lines.